Evil Eye as a cause of social conflicts and the cultural status of the Manaas, a Marginalized potter subgroup of the Dawuro ethnic Community, Southwest Ethiopia - Genbezo, Dubale Gebeyehu; Tena, Misrak; Gatiso, Mellese Mada (Indonesian Journal of Education and Social Humanities, 2024)
This study explores the perceptions of the evil eye, its consequences, and the status of the manas, a marginalized potter subgroup of the Dawuro community. The Dawuros number about a million people living in the Southwestern part of Ethiopia, the Dawuro zone, and speak the Dawuro language. The manaas are groups practicing pottery and are regarded as evil-eyed among the Dawuros. To Dawuro in general, the manaas are a low-ranking group, accused of possessing Evil Eye which is supposed to endanger the lives of others. They are by tradition the object of much marginalization, prejudice, and superstition, and continue to be discriminated against in housing, schooling, social gathering, funeral, and marriage opportunities, although they provide useful goods and various ritual services to the Dawuros. The paper employs qualitatively gathered data and discusses the perceptions of the evil eye among the Dawuros and its consequences and implications on the lives of the Manaas.